Targeted and cellular therapies in lymphoma: Mechanisms of escape and innovative strategies - Deshpande, Anagha; Munoz, Javier (Frontiers in Oncology, 2022)
The therapeutic landscape for lymphomas is quite diverse and includes active surveillance, chemotherapy, immunotherapy, radiation therapy, and even stem cell transplant. Advances in the field have led to the development of targeted therapies, agents that specifically act against a specific component within the critical molecular pathway involved in tumorigenesis. There are currently numerous targeted therapies that are currently Food and Drug Administration (FDA) approved to treat certain lymphoproliferative disorders. Of many, some of the targeted agents include: rituximab, brentuximab vedotin, polatuzumab vedotin, nivolumab, mogamulizumab, vemurafenib, crizotinib, ibrutinib, cerdulatinib, idelalisib, venetoclax, tazemetostat, and CAR T-cells. Although these agents have shown strong efficacy in treating lymphoproliferative disorders, the complex biology of the tumors have allowed for the malignant cells to develop various mechanisms of resistance to the targeted therapies. Some of the mechanisms of resistance include downregulation of the target, antigen escape, increased PD-L1 expression and T-cell exhaustion, mutations altering the signaling pathway, and agent binding site mutations. In this manuscript, we discuss and highlight the mechanism of action of the above listed agents as well as the different mechanisms of resistance to these agents as seen in lymphoproliferative disorders.